Pyrolysis of lignin obtained from cinnamyl alcohol dehydrogenase (CAD) downregulated arabidopsis thaliana - Kwang Ho Kim; Jae-Young Kim; Chang Soo Kim; Joon Weon Choi (Korean Society of Wood Science Technology, 2019)
Despite its potential as a renewable source for fuels and chemicals, lignin valorization still faces technical challenges in many aspects. Overcoming such challenges associated with the chemical recalcitrance of lignin can provide many opportunities to innovate existing and emerging biorefineries. In this work, we leveraged a biomass genetic engineering technology to produce phenolic aldehyde-rich lignin structure via downregulation of cinnamyl alcohol dehydrogenase (CAD). The structurally altered lignin obtained from the Arabidopsis thaliana CAD mutant was pyrolyzed to understand the effect of structural alteration on thermal behavior of lignin. The pyrolysis was conducted at 400 and 500 °C using an analytical pyrolyzer connected with GC/MS and the products were systematically analyzed. The results indicate that aldehyde-rich lignin undergoes fragmentation reaction during pyrolysis forming a considerable amount of C6 units. Also, it was speculated that highly reactive phenolic aldehydes facilitate secondary repolymerization reaction as described by the lower yield of overall phenolic compounds compared to wild type (WT) lignin. Quantum mechanical calculation clearly shows the higher electrophilicity of transgenic lignin than that of WT, which could promote both fragmentation and recondensation reactions. This work provides mechanistic insights toward biomass genetic engineering and its application to the pyrolysis allowing to establish sustainable biorefinery in the future. ？ 2019, Korean Society of Wood Science Technology. All rights reserved.